2016
DOI: 10.1080/01635581.2017.1247885
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 mRNA Is Downregulated in the Liver of Pancreatic Cancer Patients Suffering from Cachexia

Abstract: We speculate that suppression of IL-4 is involved in cancer cachexia, although the exact mechanisms have to be further elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Our knowledge about hepatic inflammation in human cancer cachexia is particularly scarce. Previous studies reported liver macrophage infiltration and down‐regulation of IL‐4 gene expression in liver sections of cachectic pancreatic cancer patients 64,65 . A mild cholestasis was documented in a cohort of cachectic and non‐cachectic patients with various cancer types and was characterized by an increase in serum levels of alkaline phosphatase and gamma‐glutamyl transpeptidase 66 .…”
Section: Discussionmentioning
confidence: 94%
“…Our knowledge about hepatic inflammation in human cancer cachexia is particularly scarce. Previous studies reported liver macrophage infiltration and down‐regulation of IL‐4 gene expression in liver sections of cachectic pancreatic cancer patients 64,65 . A mild cholestasis was documented in a cohort of cachectic and non‐cachectic patients with various cancer types and was characterized by an increase in serum levels of alkaline phosphatase and gamma‐glutamyl transpeptidase 66 .…”
Section: Discussionmentioning
confidence: 94%
“…IL-4 was lower in the more cachectic G68 group. IL-4 mRNA has previously been shown to be downregulated in the liver of pancreatic cancer patients suffering from cachexia [24]. GRO is known to increase muscle fatty acid oxidation contributing to the breakdown of muscle [25].…”
Section: Discussionmentioning
confidence: 99%
“…IL4 has also been shown to recruit myoblasts to form mature myotubes, and further studies have demonstrated that this cytokine can exert a pro‐migratory effect in vitro . Interestingly, in pancreatic cancer patients affected by cachexia, IL4 messengers are down‐regulated in liver and muscle …”
Section: Introductionmentioning
confidence: 99%